Organizational Justice and Organizational Citizenship Behavior with Leader-Member Exchange as Mediation - Ryan Eka; Adi Rahmat; Ririn Handayani (SAINS ORGANISASI, 2022)
The purpose of this study is to find out that organizational justice affects OCB with LMX as a mediation. This study will also examine the relationship between these variables in the object of research, namely the Rokan Hilir (Rohil) Resort Police (Polres). This research will be conducted on members of the Rohil Police Station. The design of this research is to assemble the relationship between three variables, namely organizational justice, LMX and OCB. The result of this research is that organizational justice is influential or dominant on organizational citizenship behavior for members of the Rokan Hilir Police Station where the better the organizational justice, the OCB will increase. On the perception of members of the Rokan Hilir Police Station to increase the leader-member exchange (LMX) variable, which is defined as a workplace socialization network, we must improve organizational justice. And also the leader-member exchange is stated to be able to mediate the effect of organizational justice on organizational citizenship behavior.